The high-potential leader : how to grow fast, take on new responsibilities, and make an impact - Charan, Ram (Hoboken : Wiley, 2017)
"Companies need High Potential leaders (Hi-Po’s) more than ever before to help them adapt to todays tumultuous, digitally-driven business environment. If you meet the Hi-Po criteria, you're in high demand--and this book explains how to fast-track yourself. Criteria for Hi-Pos are changing markedly. In the past, fast-track leaders were tapped mainly because of their cognitive abilities, analytical skills, imagination, thoroughness in finding solutions and even perfectionist tendencies. In the new climate, other attributes will count more heavily: relationship skills, experience, judgment, abilities to engage, motivate, and draw out the best performance in others, strategic skills and even personal habits and behavior style. Above all, companies see Hi-Pos as people who have the capacity to grow quickly and step into new leadership roles competently. This book is a step by step guide to becoming a high potential leader"--
"Companies need High Potential leaders (Hi-Po's) more than ever before to help them adapt to todays tumultuous, digitally-driven business environment. If you meet the Hi-Po criteria, you're in high demand--and this book explains how to fast-track yourself. Criteria for Hi-Pos are changing markedly. In the past, fast-track leaders were tapped mainly because of their cognitive abilities, analytical skills, imagination, thoroughness in finding solutions and even perfectionist tendencies. In the new climate, other attributes will count more heavily: relationship skills, experience, judgment, abilities to engage, motivate, and draw out the best performance in others, strategic skills and even personal habits and behavior style. Above all, companies see Hi-Pos as people who have the capacity to grow quickly and step into new leadership roles competently. This book is a step by step guide to becoming a high potential leader"--
Machine generated contents note: 1 High-Potential Leaders Are Crucial to Helping Businesses Adapt and Thrive in the Digital Age 1 The Urgent Need for High-Potential Leaders 1 What "High Potential" Means Now 2 An Important Distinction 7 Getting Hipos There Faster 8 How Hipos Can Use This Book 11 How Leadership Developers Should Use This Book 13 A Final Word 14 Tips for Hipos--How to Use This Book 18 Tips for HR and Leadership Developers--How to Use This Book 20 PART I Five Essential Skills for High-Potential Leaders 23 2 Increase the Return on Your Time (ROYT) 25 Get Comfortable with People Better Than You 25 Set and Reset Your Priorities 28 Customize Your Information Flow 31 Delegate and Follow Through 33 Trust But Verify 34 Decide How to Leverage Yourself 35 Create Repeatable Processes 37 Be Decisive 38 Additional Resources 43 3 Multiply the Energy and Skills of Those Around You 45 Identify a Person's God-Given Talent 46 Build Other People's Strengths 50 Make Necessary Changes Quickly 52 Manage the Intersections 53 Lead the Dialogue 56 Be a Social Architect 58 How Tony Palmer Became a Talent Magnet 60 Additional Resources 68 4 Be a Master of Big Ideas and Execution 71 Make Your Big Ideas Better 71 How to Assess Your Good Ideas 72 Getting Big Ideas Executed 76 Execution Basics 78 The Art of Asking Incisive Questions 80 A Hipo's Vision and Execution at Fingerhut 81 Additional Resources 90 5 Get to Know Customers, Competitors, and the Macro Environment 91 Observe the End-to-End Consumer Experience 92 Know the Competition 94 Dissect Ecosystems 98 See Your Business from the Outside In 100 Keep Up with Technology 103 Additional Resources 108 6 Build Your Mental Capacity 109 Widen Your Lens 109 Keep Learning 111 Build Diverse Networks 114 Seek Information from Everywhere 116 Stay Mentally Flexible 120 Additional Resources 129 PART II Taking Charge of Your Growth and Choosing Your Next Big Career Move 131 7 How, When, and Why to Make a Leap 133 The Virtue of Leaps 134 Making Leaps Without Leaving Your Company 139 Build Your Own Support System 141 Bonnie Hill's Multiple Leaps 143 Leaps Outside the Company 146 Weighing a Job Change 148 Your Exit Plan 150 Your Entrance Plan 151 Additional Resources 159 8 Track Your Mental Health and Work/Life Balance 161 Business Achievement 162 Life Satisfaction 163 Find a Meaningful Focus 168 Protect Your Mental Health 172 How Aaron Greenblatt Found His Focus 173 Additional Resources 181 PART III The Care and Feeding of High Potentials--Every Organization's Precious Resource 183 9 Identifying, Recruiting, and Retaining Hipos 185 Redefi ne and Find High-Potential Leaders 186 Create Opportunities for Growth 189 Clear the Path for Hipos 192 Improve Feedback Loops 193 Refresh the Leadership Pool 196 How to Use This Book to Develop Your Organization's Hipos 197 Key Points for Talent Management Leaders 197 Additional Resources 209 Acknowledgments 211 Index 213.
Includes index.
Keywords: Leadership; Communication in management; Employee motivation; BUSINESS & ECONOMICS / Leadership